Language and Empiricism - After the Vienna Circle - Chapman, S. author. aut Link
V, 191 p.
Keywords: The author offers a new assessment of the influence of the Vienna Circle on language study, and considers its relevance to the debate in present-day linguistics about the relative merits of 'intuitive' and 'real life' sources of data.